Community Pest Management in Practice A Narrative Approach - Howard, Tanya M.; Alter, Theodore R.; Frumento, Paloma Z.; Thompson, Lyndal J. (Springer Nature Singapore : Imprint: Springer, 2019)
This book presents a collection of practitioner and community stories that reveal how invasive species management is a community issue that can spark community formation and collective action. It combines the unique first-person narratives of practitioners on the frontline of invasive species management in Australia with three case studies of community action for wild dog management across a range of geographical landscapes. The book offers readers a new understanding of how communities are formed in the context of managing different species, and how fundamental social and political processes can make or break landholders' ability to manage invasive species. Using narrative analysis of practitioner profiles and community groups, drawing lessons from real-world practices, and employing theories from community development, rural sociology and collective action, this book serves multiple functions: it offers a teaching tool, a valuable research contribution, and a practitioner's field guide to pursuing effective community development work in connection with natural resource management, wildlife management and environmental governance. .